2020
DOI: 10.1016/j.jsxm.2020.05.004
|View full text |Cite
|
Sign up to set email alerts
|

Practices and Barriers in Sexual History Taking: A Cross-Sectional Study in a Public Adult Primary Care Clinic

Abstract: Background Surveys report low frequencies of sexual history (SH) obtained in primary care. Sexually transmitted infections incidence can be reduced with timely screening. It is important to determine whether providers obtain thorough SH and to identify needs for improvement. Aim To evaluate the frequency and depth of SH taking in primary care. Methods In this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 16 publications
1
24
0
Order By: Relevance
“…22 However, a cross-sectional study in the USA on documentation of sexual history taking in primary care found partial sexual history taking in 34%, and none in the other 65% of the primary care consultations. 15 A South African study found that the prevalence of non-communicable disease and HIV infection is high, and that community-based screening must be expanded. 25 This prompted the researcher's interest in understanding what the nature of sexual history taking entails in a rural primary care setting in South Africa.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…22 However, a cross-sectional study in the USA on documentation of sexual history taking in primary care found partial sexual history taking in 34%, and none in the other 65% of the primary care consultations. 15 A South African study found that the prevalence of non-communicable disease and HIV infection is high, and that community-based screening must be expanded. 25 This prompted the researcher's interest in understanding what the nature of sexual history taking entails in a rural primary care setting in South Africa.…”
Section: Introductionmentioning
confidence: 99%
“…A sexual history usually covers sexual practices, partners, previous STI, prevention of STI and pregnancy, and other factors such as sexual wellbeing, trauma, gender identity, sexual orientation, and other sexual concerns. 14 , 15 In the literature, there is an emphasis on a culturally sensitive and respectful sexual history taking, where good communication and an inclusive attitude are important. 16 When taking a sexual history, lay terminology makes it easier for doctors and patients, not only in terms of concepts, but also to ease the discussion or patient-doctor interaction.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, GPs often find it difficult to talk about their patients' sexual problems, and do not include sexual history taking in their routine practice 11 . The rate of sexual history taking in primary care is low and depends on the patient's age and GP's training level and gender 12 .…”
Section: Introductionmentioning
confidence: 99%
“…10,11 Strategies to reverse STI trends will require expansion of routine STI testing and treatment beyond sexual health service platforms and integration into other health services. 12 Integrating sexual and reproductive health (SRH) into other health services poses challenges at many health-system levels including the provider level. 10,11,13 Graduate medical education, in which resident physicians complete mentored-training, is an opportunity to improve provider delivery of STI screening and treatment as physicians establish medical practices that continue throughout their professional careers.…”
mentioning
confidence: 99%